2018
DOI: 10.1172/jci99424
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of inflammation and tumor microenvironment to neurofibroma tumorigenesis

Abstract: Neurofibromatosis type 1 associates with multiple neoplasms, and the Schwann cell tumor neurofibroma is the most prevalent. A hallmark feature of neurofibroma is mast cell infiltration, which is recruited by chemoattractant stem cell factor (SCF) and has been suggested to sustain neurofibroma tumorigenesis. In the present study, we use new, genetically engineered Scf mice to decipher the contributions of tumor-derived SCF and mast cells to neurofibroma development. We demonstrate that mast cell infiltration is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 55 publications
3
97
0
6
Order By: Relevance
“…Previous studies suggested that NF1 heterozygosity in the cellular microenvironment (particularly in mastocytes) was necessary for initiation and development of cNFs (27). However, more recent studies performed in mice and humans suggest that heterozygosity in mastocytes is dispensable for tumor development (28). Our observations are consistent with these latter findings, as NFs develop in both Nf1 +/− and wild-type backgrounds.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies suggested that NF1 heterozygosity in the cellular microenvironment (particularly in mastocytes) was necessary for initiation and development of cNFs (27). However, more recent studies performed in mice and humans suggest that heterozygosity in mastocytes is dispensable for tumor development (28). Our observations are consistent with these latter findings, as NFs develop in both Nf1 +/− and wild-type backgrounds.…”
Section: Discussionsupporting
confidence: 91%
“…In a PLP-CreERT2 pNF model, we have previously demonstrated that Schwann cells are susceptible to pNF development when Nf1 is ablated with tamoxifen induction at the immature Schwann cell stage (new born) 31 . In the course of a study on the role of the stem cell factor in pNF development using the PLP CreERT2; Nf1 f/f mice 32 , our lab observed that some pNF further transformed into MPNST spontaneously (Fig. 4a, b ).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the role of mast cells in pathogenesis has become a subject of raising interest. Especially, a growing body of evidence indicates that mast cells are implicated in tumor development [68][69][70][71][72][73]. Indeed, these cells are known to favor immunologic tolerance and secrete both growth and angiogenic factors which enhance tumor expansion [74][75][76].…”
Section: Mast Cells In Pathophysiology Of Hyperaldosteronismmentioning
confidence: 99%